Частота мутації CCR2-64I гена хімокінового рецептора CCR2, що асоціюється з уповільненням прогресування СНІДу серед жителів західного регіону України - Тиркус, М.Я. (Фактори експериментальної еволюції організмів, 2013)
Aims. The rate of progression of HIV-1 disease exhibits a remarkable variation among different individuals. Several natural polymorphisms in the genes for the human CC-chemokine receptors CCR5 and CCR2 are associated with HIV-1 disease. associated with a delayed progression to disease. The aim of this study was to determine the frequency of chemokine receptor gene mutation CCR2-64I in people from Western region of Ukraine. Methods. DNA from the above samples was isolated using a modified salting out method. Extracted DNA was amplified by Polymerase chain reaction (PCR). The PCR products were subsequently digested with the restriction enzyme Bse8 I and subjected to electrophoresis in a 2 % agarose gel. Results. A molecular genetic study of chemokine receptor gene mutation CCR2-64I performed in 147 people from Western region of Ukraine. The frequency of CCR2-64I heterozygote was 12.92 % and the frequency of CCR2-64I homozygous was 1.36 % іn the studied group. CCR2-64I mutation were more frequently in group of women (16.9 %) than in group of men (8.6 %). Conclusions. The results show relatively high genetic resistance to HIV infection in people from Western region ofUkraine.

Key words: HIV infection, chemokine receptor, mutation.